The Guidewire-assisted Drainage Catheter Placement in Chronic Subdural Hematoma - Zheng, Bingjie; Wang, Chunlei; Yao, Jinbiao; Zhu, Shiyi; Meshcheryakova, Svetlana; Shi, Huaizhang (Frontiers in Surgery, 2022)
Background Chronic subdural hematoma (cSDH) is a common neurosurgical pathology associated with older age. The burr hole drainage is a predominant technique with a lower incidence of recurrence and morbidity. The blind placement of the subdural drain could result in intracerebral hemorrhage. This paper describes a simple and reliable technique for drainage catheter placement in cSDH to reduce intracerebral hemorrhage. Methods Forty-nine consecutive patients with cSDH were treated with The Guidewire-assisted Drainage Catheter Placement Technique between July 2019 and June 2021. Epidemiological, clinical and radiographical data were collected and reviewed. The operative technique consists of an angular guidewire tip and catheter. Under the navigation of the guidewire, the catheter is inserted into the subdural space and the length of catheter remaining in the subdural space was 4–5 cm. The catheter was tunneled subcutaneously and fixed at the point where it emerged from the scalp. Results Forty-nine consecutive patients underwent 55 The Guidewire-assisted Drainage Catheter Placement. The gender distribution was 37 men and 12 women. The mean age was 69.3 years. The patients presented with headache (31 patients), weakness of limbs (28 patients), speech disturbances (7 patients), and Altered behavior (6 patients). Neither intracerebral hemorrhages nor post-operative seizure occurred. Forty-seven patients were improved after the operation. The recurrence occurred in one patient. Conclusions The Guidewire-assisted Drainage Catheter Placement Technique is a reliable method for the insertion of a subdural catheter to evacuate of the Chronic Subdural Hematoma，and is associated with an extremely low risk to cortical structures and cerebral veins.